Comparison of learning management system platforms for choosing a suitable platform for users in research administration - Alva A. (2021)
The present paper is a comparison of three types of e-learning management systems. In the research administration of the University of Sciences and Humanities, a platform of online courses is aimed to achieve training and project courses that will be focused on the institution's researchers. For this purpose, it is necessary to use tools adapted to the way of working that are user-friendly and can be adapted to the users' requirements. Therefore, the three platforms' comparison was performed by measuring the following points: Description of the platforms' characteristics, description of the functionality, and the comparative analysis. This research is made to be implemented in the Image Processing Research Laboratory (INTI-Lab) server and to use the platform at the beginning of the year 2020. Online courses have become a tool that allows people to obtain knowledge rapidly, and as researchers, to adapt to these modalities makes the distribution of information faster and easier. © 2021 Seventh Sense Research Group®.